Sanitation challenges, groundwater perspectives and their intertwined relationships in Kisumu, Kenya - Kanoti, Japhet; Olago, Daniel; Akech, Nobert; Nyamoi, Christopher; Dulo, Simeon; Ayah, Richard; Taylor, Richard (University of Nairobi, 2020)
This research under the AfriWatSan project assessed groundwater and sanitation challenges based on field surveys, sampling, analyses, and interviews, as well as reviews of the literature and historical borehole data in Kisumu, Kenya. Previous studies in the area have shown that the number of shallow wells, buildings, unimproved pit latrines and sanitary risks have increased tremendously between 1999 and 2019. This study confirmed that the main water and sanitation challenges in Kisumu are (1) inadequate, poor and deteriorating water quality, (2) poor waste disposal management systems, and (3) poor sanitation services. There is a need for the introduction of new and sustainable groundwater approaches supported by science and decision-making processes that involve all stakeholders. Current deficiencies in the provision of adequate water and dignified sanitation to the poor in Kisumu can be remedied through improved knowledge of shallow aquifer dynamics and innovative research. It was noted that apart from the donor agencies and multi-national NGOs, private investors are unwilling to invest in water projects in Kisumu due, in part, to government legislation that constrains the cost that may be levied on water.